2011
DOI: 10.1021/ja2040738
|View full text |Cite
|
Sign up to set email alerts
|

Catching the First Oligomerization Event in the Catalytic Formation of Polyaminoboranes: H3B·NMeHBH2·NMeH2 Bound to Iridium

Abstract: We report the first insertion step at a metal center for the catalytic dehydropolymerization of H(3)B·NMeH(2) to form the simplest oligomeric species, H(3)B·NMeHBH(2)·NMeH(2), by the addition of 1 equiv of H(3)B·NMeH(2) to [Ir(PCy(3))(2)(H)(2)(η(2)-H(3)B·NMeH(2))][BAr(F)(4)] to give [Ir(PCy(3))(2)(H)(2)(η(2)-H(3)B·NMeHBH(2)·NMeH(2))][BAr(F)(4)]. This reaction is also catalytic for the formation of the free linear diborazane, but this is best obtained by an alternative stoichiometric synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
109
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(116 citation statements)
references
References 32 publications
7
109
0
Order By: Relevance
“…It belongs to the monoclinic Pn space group (Table S1w). All N-B bond distances and bond angles are comparable with those observed in the gauche form and other reported B-N chain anion compounds, [14][15][16][17] and fall within the normal range (Table S2w). The striking feature of the molecular structure is that DDAB adopts an anti, rather than gauche, conformation (Fig.…”
Section: 2supporting
confidence: 85%
See 2 more Smart Citations
“…It belongs to the monoclinic Pn space group (Table S1w). All N-B bond distances and bond angles are comparable with those observed in the gauche form and other reported B-N chain anion compounds, [14][15][16][17] and fall within the normal range (Table S2w). The striking feature of the molecular structure is that DDAB adopts an anti, rather than gauche, conformation (Fig.…”
Section: 2supporting
confidence: 85%
“…To 16 In these structures, free MeNH 2 BH 2 NHMeBH 3 adopts anti (III) form and all others adopt gauche form (Table S4w). Intermolecular dihydrogen bonds were observed in structures I and II as well as dimeric structures of the two gauche forms; 14,15 and an intramolecular dihydrogen bond was observed in structure IV.…”
Section: 2mentioning
confidence: 98%
See 1 more Smart Citation
“…The Ir– H were located in the final difference map, while the bridging B– H –Ir were not located with any reliability and placed in calculated positions. The Ir···B [2.217(4) Å], B1–C1 [1.588(6) Å] and B1–N1 [1.605(6) Å] distances are all consistent with an amine–borane taking part in two Ir···H–B 3 center–2 electron interactions, comparing closely with sigma complexes of H 3 B·NMe 3 with the same metal fragment [Ir···B, 2.207(7) Å], [17] H 3 B·NMeH 2 [2.210(7) Å] [33] and H 3 B·NH 3 [2.209(5) Å]. [18] Amine–boranes acting in a monodentate bonding mode through a single B–H bond, or as B–H activated boryls, show significantly longer (ca.…”
Section: Resultsmentioning
confidence: 63%
“…Weller and Manners have since reported that the diborazane H 3 B · NMeHBH 2 · NMeH 2 , the product of one dehydrooligomerisation of H 3 B · NMeH 2 , can be formed by catalytic methods [33], and its role as a possible intermediate in dehydropolymerisation has been further explored (see Sect. 2.8.3) [28].…”
Section: Aminoboranes: Observation and Trappingmentioning
confidence: 99%